Adenosine and High-intensity Interval Training as Potential Therapies on Free Fatty Acids and Metabolic Factors in High-fat Diet-Induced Obesity in Male Wistar Rats : Adenosine and HIIT on Metabolic Factors - Eslami, Zahra; Fallah, Ayda; Eghbal Moghanlou, Abdorreza; Baydaş, Giyasettin; Sharifian, Shohreh; Mirghani, Seyed Javad (Iranian Journal of Pharmaceutical Sciences, 2025)
Obesity, caused by an inequality between energy production and consumption, is characterized by lipid accumulation in adipose tissues. Currently, around 650 million adults and roughly 340 million children and adolescents (aged 5-19 years) are affected by obesity. This condition tends to be more common among women and older populations. It is imperative to develop uncomplicated therapeutic approaches to prevent obesity-related metabolic diseases in conjunction with lifestyle modifications. Forty-three rats were randomly divided into five groups: 1. normal diet (ND), 2. High-fat diet (HFD), 3. HFD + adenosine, 4. HFD + High-intensity interval training (HIIT) + adenosine, and 5. HFD + HIIT. Gene expression of CGI-58, HSL, and AMPK in subcutaneous adipose tissues and serum level of glucose, insulin, Homeostatic Model Assessment for Insulin Resistance (HOMA-IR), free fatty acid (FFA), and lipid profile (Triglyceride (TG), Total cholesterol (TC), Low density lipoprotein (LDL), High density lipoprotein (HDL), and Very low density lipoprotein (VLDL)) were assessed. The rats were fed HFD-induced obesity for 13 weeks. Following, adenosine 0.2 mg/ml/kg and 0.4 mg/ml/kg, as well as HIIT, were administered over 12 weeks. CGI-58, HSL and AMPK gene expression showed significant expression in all groups. HFD+HIIT+adenosine, HFD+adenosine, and HFD+HIIT groups significantly increased all genes. Conversely, FFA and glucose serum levels were significantly reduced in intervention groups. Insulin had higher serum levels in ND, HFD + adenosine, and HFD+HIIT groups, and adenosine caused decreased glucose. Also, favorable effects of HIIT and adenosine on lipid profile were observed. HIIT and adenosine can affect lipid metabolism, improve insulin resistance, and increase lipolysis in adipose tissue. Furthermore, adenosine can boost the effect of HIIT on gene expression, triggering lipolysis to prevent obesity.